Gonçalves De Magalhães, Político E Historiador - Silva, Lillian Micheli [UNIFESP] (2018)
This research has a goal the analyze of the actuation of Domingos Gonçalves de Magalhães in less studied fields when talking about the poet: in politics and in the beginnings of the historiography in Brasil, in particular moments of the Brasil Império. In the politic field, Magalhães exert many important roles. Participated in the contention of two revolts in the Empire – Balaiada and Farroupilha- exercising the role of government secretary, was a Brazilian diplomat in several countries for more than thirty years. As a man of letters, was member of the IHGB and professor in the Colégio D. Pedro II, besides actively participating in the production of the main Brazilian literary magazines and to have his works referenced by contemporaries. Thus, we will seek in this research to understand the political connections of Magalhães and his conceptions about the Brazilian nationality, reflecting about the alliances signed by the poet in different areas and during troubled moments of the Brazilian nineteenth century.